Exploring the Pragmatic Relationship Between Word Meaning and Textual Content in a Scientific Paper - Paronyan, Shushanik (Bulletin of Yerevan University B: Philology, 2023)
The ultimate goal of any communicative act is to create meaning. The meaningful combination of language units creates the overall content of oral or written communication and realizes the communicative intent of the writer or speaker.  The aim of the present article is to study how the communicative intent of the writer unfolds through the use of words having a specific semantic component as part of the lexical meaning. Words that have a negative semantic component as part of denotative meaning as well as phrases which contain one or more words with negative denotative meaning have been picked out from the article “Genocide” by R. Lemkin[1] and studied.  The communicative-semantic and pragmatic analyses of the practical material has revealed that with the help of the words and phrases containing negative referential meaning, the author creates a convincing and powerful content and achieves his goal, which is to condemn genocidal activities.[1] R. Lemkin, Genocide // American Scholar, Vol. 15, no. 2, 1946, էջ 227-230:
Keywords: semantics; lexicology; word meaning; denotation; persuasion; genocide; communicative-pragmatic approach